Studi Tentang Guru Yang Telah Bersertifikasi Kompetensi Dalam Meningkatkan Motivasi Belajar Siswa - Mochammad Nurfadilah; Santoso Sri Handoyo (Jurnal Pensil : Pendidikan Teknik Sipil, 2015)
This study aims to find a teacher who has certified competencies in enhancing studentâ€™s motivation in class grade XI building drawing engineering program in SMK 26 Jakarta.            Place of research conducted in class grade XI building drawing engineering program year 2010/2011 in SMK 26 Jakarta. The research method is descriptive research method with a survey approach with 50 samples of student. Data increase studentâ€™s motivation is obtained through a questionnaire with Likert scale. The results showed that 34 grains obtained valid and true statement.            The results of this study was obtained by converting the average score in the rating scale between 1 (very low) to 4 (very good), 4 indicators of interpretation has declared open communication among less well at 2.49, a prerequisite for 2.25, novelty at 2.34 and pleasant conditions of 2.50. Meanwhile, four other indicators of interpretation has expressed good enough for them meaningfulness 2.91, 2.80 for modeling, training / practice an active and useful for training are divided by 2.68 and 2.95.            The conclusion of this study is overall of eight indicators that the parameters a certified teacher effort in improving student's motivation is still not meet the standards of good or satisfaction. Need to be repaired and enhanced the performance or the ability of teachers to teach in the process of teaching and learning activity in the classroom in order to produce a better quality of teaching and learning activity in the classroom and more satisfactory learning outcomes